PENGEMBANGAN MEDIA PEMBELAJARAN FISIKA BERBASIS ADOBE FLASH UNTUK MENJELASKAN FISIKA INTI DAN RADIOAKTIVITAS UNTUK SMA KELAS XII - Anwar Basyari; Sunaryo Sunaryo; Bambang Heru Iswanto (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2012)
This research is underway to create a media that can be clearly illustrate the concepts of physics which hard to describe with words. In this study retrieved chapters of atomic nuclear and radioactivity. Media created is a computer-based media with a multimedia system, so that the subject are hard to describe in the abstract words can be illustrated by using animated or moving images. Multimedia system allows audio, and visual merging, as well as allow for interaction between students with computers that makes learning more meaningful. The study produced a learning program with a multimedia system that can be directly used by students or teachers as a tool in the learning process. The program is created using Adobe Flash animation software that is assisted by several other supporting software. Keywords: making, multimedia, atomic nuclear, radioactivity, physics.